A proposed utilization model for mobile learning in Sultan Qaboos University - Mohammad Al Tabib, Shaima; Mohd Daud, Shaffe; Mohd Ayub, Ahmad Fauzi; Mahmud, Rosnaini; Moustafa Qoussini, Alla Edein (American-Eurasian Network for Scientific Information, 2016)
The use of mobile devices for learning purposes gains an increasing interests, this is because mobile learning extends the education process to anytime/ anywhere concept. On the other side, there is a lack of comprehensive understanding and identification of the factors affecting mobile learning education in higher institutions. Despite the availability of studies on mobile learning adoption, its theoretical foundations have not yet matured. In addition, studies on mobile learning adoption and utilization in the context of Oman are also still very limited. Against this concern, this study was undertaken with the aim of investigating factors that could influence mobile learning utilization in Sultan Qaboos University. In this article a model of mobile learning utilization was proposed, this model is built based on Unified Theory of Acceptance and Use of Technology (UTAUT) and Mobile Learning Acceptance Model (MLAM), in this model performance expectancy, effort expectancy, facilitating conditions, social sciences and mobile self-management acts as predicting factors of mobile learning utilization, while gender and field of study included as a moderators. Finally, since this is an in going research, the model will hopefully provide a framework for future work and investigation to collect and analysis of data to prove the validity and suitability of the model. The present study provides both a theoretical and practical contributions in understanding the predictors of intention to adopt and utilize mobile learning in Oman, and it should be of interest to both researchers and practitioners in the higher education field.